Zulu and Xhosa praise-poetry and song - Rycroft, David K. (International Library of African Music, 1962)
The boundary between song and some forms of verse or declamation which are nowadays classified as "oral literature" is a blurred one and calls for co-operation between linguists and ethnomusicologists. Very little study has yet been made of musical characteristics found in the border-line art of praise-poetry or praise-singing which is practiced very widely throughout Africa. Among the Eastern and South-Eastern Bantu, what small evidence there is reveals considerable differences between the traditional style of delivery associated with Zulu izibongo praises, and that, for example, of the Heroic Recitations of the Banyankore, a Bantu people of East Africa. A.N. Tucker has recorded some of the latter and they were taken as the subject for a thesis by H.F.R. Morris. They are uttered with quite phenomenal rapidity and the overall intonation contour of each line is a gradually descending one, without the observance of fixed musical pitches.
Keywords: Zulu (African people); Xhosa (African people); Laudatory poetry; Ethnomusicology; African Music